2011
DOI: 10.4269/ajtmh.2011.11-0058
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Sources of Toxoplasmosis among Orang Asli (Indigenous) Communities in Peninsular Malaysia

Abstract: This study aims to evaluate the current seroprevalence of toxoplasmosis among indigenous communities in Peninsular Malaysia and relate its association with epidemiological data. Overall seroprevalence of Toxoplasma gondii was 37.0% with 31.0% immunoglobulin (Ig) G, 1.8% IgM, and 4.2% seropositivity for both anti-Toxoplasma antibodies. Multivariate analysis showed that age above 12 years (odds ratio [OR] = 2.70, 95% confidence interval [CI] = 1.75–4.04, P < 0.001), using untreated river and mountain water su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 32 publications
6
30
1
Order By: Relevance
“…On the other hand the highest (05 %) sero-positivity for IgG+IgM is seen in age group16-30 and 46-60. The work of Ngui is in agreement with the present results (Table 3), who also recorded highest IgG sero-positivity than IgM and IgG+IgM [34]. While Mohan reported highest (10%) IgM positivity in 6-12 years age group in urban area and 17.7% highest IgM positivity in age less than or equal to 05 years in the rural area [35].…”
Section: Risk Factors For Transmissionsupporting
confidence: 91%
“…On the other hand the highest (05 %) sero-positivity for IgG+IgM is seen in age group16-30 and 46-60. The work of Ngui is in agreement with the present results (Table 3), who also recorded highest IgG sero-positivity than IgM and IgG+IgM [34]. While Mohan reported highest (10%) IgM positivity in 6-12 years age group in urban area and 17.7% highest IgM positivity in age less than or equal to 05 years in the rural area [35].…”
Section: Risk Factors For Transmissionsupporting
confidence: 91%
“…Toxoplasmosis is not exclusive to marginalized communities, but it may have a greater impact on such communities for the reasons argued below. Studies in Malaysia have reported infections (seroprevalence) in healthy individuals (13.9–30.2%) [32–34], pregnant women (23.0–31.6%) [35–38], HIV patients (21.0–41.2%) [20, 39–41], newborn babies (2.0%) [42] and indigenous communities (10.6–37.0%) [43, 44]. In Southeast Asia, seroprevalence varies from < 2% up to 70% [45].…”
Section: Discussionmentioning
confidence: 99%
“…The most common feature is focal retinitis or chorioretinitis, where it can manifest as either localized necrotizing retinitis with inflammation of subjacent choroid or an active creamy-white focal retinal lesion 6. In Malaysia, the seroprevalence of T. gondii is estimated to be around 37.0% for antitoxoplasmosis antibodies 7. Serological testing for specific antibodies has been used as laboratory evidence of the disease, but titration of these antibodies has low reliability in ocular toxoplasmosis.…”
Section: Introductionmentioning
confidence: 99%